Acceptability of hamburger using coconut as filler - Santos, Ma. Eleanor M.
The most acceptable level of "buko" (young coconut if the "mala-kanin" stage) meat in hamburger was 50% as evaluated by a panel of ten members based on flavor, texture and general acceptability. Varying the levels of cornstarch but maintaining the one to one ratio of "buko" to the beef-pork mixture, the panelists were asked to evaluate the binding effect of starch on the buko burger and to comment in its flavor. Results show that 14 g (7%) of cornstarch per 200 g buko burger produced the desirable intactness without any detectable starchy flavor. The protein and crude fiber content of the buko burger and the all-meat burger were analyzed. The buko burger contained 13.61% protein and 0.48% crude fiber while the all-meat burger contained 25.15% protein and 0.04% crude fiber. A one-month frozen storage target period was set for the two burgers. Every week, a sample lot of each was cooked and evaluated by he panelists based on intactness, texture, flavor and general acceptability. Tests on water-holding capacity, extract release volume and microbial load were done on the raw samples. During the one-month storage, both sets of burgers' general acceptability decreased, intactness remained almost the same, water holding capacity decreased, extract release volume increased and microbial load increased bu stayed within the standard limit.